Examining the Choroid in Ocular Inflammation: A Focus on Enhanced Depth Imaging. (15th June 2014) - Baltmr, Abeir; Lightman, Sue; Tomkins-Netzer, Oren
Abstract : The choroid is the vascular layer that supplies the outer retina and is involved in the pathogenesis of several ocular conditions including choroidal tumors, age related macular degeneration, central serous chorioretinopathy, diabetic retinopathy, and uveitis. Nevertheless, difficulties in the visualization of the choroid have limited our understanding of its exact role in ocular pathology. Enhanced depth imaging optical coherent topography (EDI-OCT) is a novel, noninvasive technique that is used to evaluate choroidal thickness and morphology in these diseases. The technique provides detailed objective in vivo visualization of the choroid and can be used to characterize posterior segment inflammatory disorders, monitor disease activity, and evaluate efficacy of treatment. In this review we summarize the current application of this technique in ocular inflammatory disorders and highlight its utility as an additional tool in monitoring choroidal involvement in ocular inflammation.